Differential Immunogenicity of mRNA-based and Inactivated Virus COVID-19 Vaccines in Patients with Inflammatory Rheumatic Disease - A Prospective Study up to 12 Months Post-3rd Dose - Nga Sze Wong; Isaac T Cheng; Tracey Yu; Vivien Chan; Tena Li; Lai-Shan Tam; Paul KS Chan; Ho So (Journal of Clinical Rheumatology and Immunology)
Background During the COVID-19 pandemic, 2 types of COVID-19 vaccines were made available in Hong Kong - the mRNA-based vaccine and the inactivated virus vaccine. All residents were required to complete 3 vaccinations. There is concern that immunogenicity acquired from COVID-19 vaccinations could be unsustainable in patients with inflammatory rheumatic disease (IRD) due to the underlying condition and immunosuppressive medication used. Therefore, this study aims to investigate the immunogenicity of COVID-19 vaccines and its sustainability in IRD patients. Methods This single-centre cohort was assembled prospectively from 8/2021 - 2/2022 in Hong Kong. Peripheral blood samples were collected from the patients before, 28 (± 3) days and 12 months after the third dose of COVID-19 vaccination. The neutralising antibody titre against the SARS-CoV-2 virus was quantified by ELISA. Results A total of 83 patients (age: 51.4± 11.7 years; 72.3% female; 17 rheumatoid arthritis, 17 psoriatic arthritis, 12 axial spondylarthritis, 37 systematic lupus erythematosus) attended all 3 visits. The vaccine distribution is summarized in Fig. 1A. Majority (96.4%) of patients had positive neutralising antibodies before the 3rd vaccine dose despite a low mean titre of 38.2± 29.7%. The antibody titre improved significantly after the 3rd dose (85.9± 23.8%) and was maintained at the 12-month visit (87.5± 22.6%). The mean antibody levels pre- and post-3rd dose were higher in patients who took mRNA-based vaccine (Fig. 1B). The presence of COVID-19 infection during the follow-up period led to significantly higher antibody titre at the 12-month visit (Table 1). There were no significant associations between immunogenicity and age, type of IRD, biologic/targeted Disease Modifying Anti-Rheumatic Drugs usage as well as additional booster doses. Conclusion 3 doses of COVID-19 vaccine produced sustained humoral response in IRD patients. The immunogenicity appeared to be dependent on the type of vaccines received in the short term and breakthrough infection in longer term.